(untitled) (Research, Society and Development, 2021)
This article seeks to analyze the process of Brazilian citizenship in the light of neoconstitutional values, inserted in an informational reality whose importance of digital networks for social movements, meetings and deliberations, produces a digital public space conducive to broad debate and information. The general objective is to develop a study on the feasibility of implementing a constitutional culture in Brazil through the promotion of citizen education, based on the neoconstitutional principles contained in the 1988 Magna Carta, envisioning a better public management in view of a better understanding by part of the population of democratic dynamics and principles. For the development of the work, bibliographical research was used with analysis of books, theses, dissertations and articles that deal with the theme. As a result of research, it was found that Brazilian citizenship, deficient by birth, needs to be re-signified in human values from an early age, in order to contribute in the medium and long term to national development in a broad and significant way, implementing the precepts of the Brazilian Constitution of 1988.